Urban-rural differentials of non-communicable diseases behavioural risk factors among adult people in northeastern Bangladesh - Akter, Sheikh Farid Uddin; Abdul Rani, Mohammed Fauzi; Rathor, Mohammad Yousuf (Northern International Medical College, 2010)
Background: The rapid social, cultural and economic changes in Bangladesh have given rise to a number of deaths that can be attributed to non-communicable diseases. The hospital records showed that death from cardiovascular diseases accounted for more than 12 percent of all deaths.